Coefficient Inequality and Coefficient Bounds for a New Subclass of Bazilevic Functions (Journal of Humanitarian and Applied Sciences, 2023)
In this paper, the researcher introduced a new generalized subclass of Bazilevic functions, which are a particular class of analytic and one to one functions defined in the open unit disc. Then a study coefficient inequality and coefficient bounds for this subclass was performed. As a result, several dervations for previous authers was obtained.
Keywords: Analyticfunctions; Bazilevic funcions; coefficient inequality; coefficient bounds; Generalization derivative operator